Comparison of velopharyngeal morphology of two palatoplasty techniques in patients with hard and soft cleft palate - Fan, Xiaofen; Liu, Weilong; Nie, Jiancun; Chen, Xiaoxuan; Dong, Yingchun; Lu, Yong (Frontiers in Surgery, 2023)
Purpose The study aims to compare the velopharyngeal morphology of hard and soft cleft palate (HSCP) patients after Furlow and Sommerlad palatoplasty. Patients and methods A total of 51 patients (20 cases in Furlow palatoplasty group, 16 cases in Sommerlad palatoplasty group and 15 normal children in the control group) were included in our study. Velopharyngeal function and speech outcomes of patients with HSCP who had either Furlow palatoplasty or Sommerlad palatoplasty for cleft palate repair were evaluated by perceptual speech assessment (PSA), lateral cephalometric radiographs and nasopharyngoscopy. To assess velopharyngeal morphology of patients treated with two techqiques, we analyzed measurements such as velar length, pharyngeal depth, and the Adequate ratio (the ratio of velar length to pharyngeal depth). Furthermore, skeletal landmarks including cranial base, cervical vertebrae, posterior nasal spine which were defined as the pharyngeal triangle were measured. Finally, the position of the point U relative to the pharyngeal triangle were compared. Results Velopharyngeal closure (VPC) rate in Furlow palatoplasty group accounted for 90%, while that in Sommerlad palatoplasty group was 81.3%. PSA of the former group was significantly better than that of the latter group (P < 0.05). Velar length, pharyngeal depth and the Adequate ratio (1.37 ± 0.14 vs. 1.41 ± 0.15) were comparable between the Furlow group and control group (P > 0.05), while Sommerlad group had a shorter velar length, deeper pharyngeal depth and a smaller Adequate ratio (1.20 ± 0.18) compared to the above two groups (P < 0.05). Furhermore, the point U of Sommerlad group in the pharyngeal triangle was higher than that of the other two groups. Conclusions In the treatment modality of patients with HSCP, both Furlow palatoplasty and Sommerlad palatoplasty seem to be effective. Furlow palatoplasty appears to have velopharyngeal morphology similar to normal control group., while Sommerlad group shows a shorter velar length, deeper pharyngeal depth and a smaller Adequate ratio